2020
DOI: 10.3390/plants9091176
|View full text |Cite
|
Sign up to set email alerts
|

Plant Soft Rot Development and Regulation from the Viewpoint of Transcriptomic Profiling

Abstract: Soft rot caused by Pectobacterium species is a devastating plant disease poorly characterized in terms of host plant responses. In this study, changes in the transcriptome of tobacco plants after infection with Pectobacterium atrosepticum (Pba) were analyzed using RNA-Seq. To draw a comprehensive and nontrivially itemized picture of physiological events in Pba-infected plants and to reveal novel potential molecular “players” in plant–Pba interactions, an original functional gene classification was performed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 105 publications
(117 reference statements)
1
27
1
Order By: Relevance
“…Pectin degradation-related genes of potato plants were regulated differentially during the infection: PGA-lyases were all downregulated, while among the genes encoding polygalacturonases and RG-I-lyases, both up- and downregulated ones were revealed ( Table S2 ). Interestingly, a similar expression pattern of pectin degradation-related genes was observed in Pba -infected tobacco plants [ 13 ]. One of the most infection-upregulated tobacco genes, LOC107816998, encoding the RG-I-lyase had the similar gene in potato (PGSC0003DMG400014600) which was also among the most upregulated ones in the course of Pba -caused infection ( Table S4 ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Pectin degradation-related genes of potato plants were regulated differentially during the infection: PGA-lyases were all downregulated, while among the genes encoding polygalacturonases and RG-I-lyases, both up- and downregulated ones were revealed ( Table S2 ). Interestingly, a similar expression pattern of pectin degradation-related genes was observed in Pba -infected tobacco plants [ 13 ]. One of the most infection-upregulated tobacco genes, LOC107816998, encoding the RG-I-lyase had the similar gene in potato (PGSC0003DMG400014600) which was also among the most upregulated ones in the course of Pba -caused infection ( Table S4 ).…”
Section: Discussionmentioning
confidence: 62%
“…In fact, we mentioned that the similar genes of potato (this study) and tobacco [ 13 ] had mostly similar expression patterns during Pba -caused infection compared to non-infected plants ( Table S4 ). This indicates that the transcriptional responses of experimental and natural hosts to Pba -caused infection are similar in general (with some unique features) at least for PCW-related genes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Pectobacteria are also known to proliferate stealthily for a while in the vascular tissues before switching to a brute force attack of surrounding tissues via the massive secretion of plant cell wall hydrolases ( Toth and Birch, 2005 ). Our previous work showed that initiation and development of the Pectobacterium -plant pathosystem requires extensive reprogramming of gene expression, both in the pathogen and its host ( Gorshkov et al, 2018 ; Tsers et al, 2020 ). Such transcriptional reprogramming obviously involves multiple transcription factors.…”
Section: Introductionmentioning
confidence: 99%